Cross‐Cultural Adaptation and Validation of the Yonsei‐Social Play Evaluation Tool (Y‐SPET) for Preschool Children in the United States: A Delphi Study. - Kim, Sarah; Lydell, Rachelle; Yoo, Sanghee; Tucker, Sarah; Hilton, Claudia; Hong, Ickpyo (Child: Care, Health & Development, 2026)
Background: This study evaluated the content validity and cultural and linguistic equivalence of the Yonsei‐Social Play Evaluation Tool (Y‐SPET), a Korean‐developed social play assessment, for preschool children in the United States. Unlike existing tools that rely on teacher reports or broad observations, the Y‐SPET is a caregiver‐rated tool that captures the nuances and qualitative aspects of Cooperative and Associative play, providing a more systematic approach to assessing peer‐based social play. Method: Using a two‐round Delphi design, 20 experts in occupational therapy, speech–language therapy and early childhood education evaluated the Y‐SPET items for linguistic and cultural appropriateness. All experts had lived in the United States for over 25 years and had extensive experience in child development. Informed consent was obtained via email from all participants prior to data collection. The Delphi procedure was conducted in two rounds with an expert panel. In Round 1 (n = 20), 36 items were evaluated on a 4‐point Likert scale and analysed using content validity ratio (CVR), convergence, consensus and stability; six items were revised. In Round 2, experts re‐evaluated the revised items (linguistic adequacy, n = 16; cultural adequacy, n = 14), and analyses of mean, standard deviation and CVR supported finalization of the 36‐item English version of the Y‐SPET (Y‐SPET‐E) in terms of content validity and linguistic and cultural appropriateness. Results: In Round 1, 20 experts evaluated the tool and found that 30 items met the cutoff criteria for content validity (CVR ≥ 0.50), convergence, consensus and stability, whereas six items did not. In Round 2, 16 experts assessed the six revised items, after which all 36 items achieved acceptable CVR values for all items (0.63–1.00), stability (CV ≤ 0.50) and strong consensus (DoCs ≥ 0.75), with mean ratings between 3.56 and 4.00. Conclusions: This study provided evidence of the linguistic and cultural appropriateness of the Y‐SPET‐E for US preschool children through a Delphi consensus process. These results contribute to the objective of providing validated assessments for advancing evidence‐based occupational therapy practice, particularly in school settings, with potential impact on both policy and research. Summary: The Y‐SPET‐E enables a standardized assessment of preschool children's social play, supporting early identification of children who may require additional support and clarifying intervention target behaviours.Assessing peer play may provide a meaningful indicator linked to school readiness, as prior research has shown associations between classroom peer play and learning behaviours/behaviour problems, and between family‐context peer play and multiple dimensions of school readiness.The Y‐SPET‐E may help monitor and support socio‐emotional readiness during the transition to elementary school by providing structured information on Associative and Cooperative play within peer interactions.Caregiver‐rated, structured results from the Y‐SPET‐E can facilitate shared decision‐making and collaborative planning across families, educators and clinicians in school‐ and community‐based services.